Modern land law - Dixon, Martin (Martin J.) (Routledge, 2023)
"Modern Land Law is one of the most current and reliable textbooks available on land law today, offering a lively and thought-provoking account of a subject that remains at the heart of our legal system. Providing an accessible approach to a complex subject, this compact textbook provides an absorbing analysis of all the key legal principles relating to land. Written with students firmly in mind, a clear introduction to every chapter frames each topic in its wider context and corresponding chapter summaries help to consolidate learning and encourage reflection. The 13th edition has been revised and brought fully up to date to address all major developments in the law, and includes key recent cases, such as Hudson v Hathway and Global 100 v Laleva in the Court of Appeal"--